Meta-Analysis: Hemodynamic Responses to Sub-anesthetic Doses of Ketamine in Patients With Psychiatric Disorders - Vankawala, Jay; Naples, Garrett; Avila-Quintero, Victor J.; Ramírez, Karina L.; Flores, José M.; Bloch, Michael H.; Dwyer, Jennifer B. (Frontiers in Psychiatry, 2021)
Ketamine, a medication traditionally used as an anesthetic, has increasingly been recognized as an effective treatment for psychiatric disorders. At sub-anesthetic doses (defined here as ≤ 0.5 mg/kg), ketamine treatment has been studied in patients with treatment-resistant depression (TRD), obsessive-compulsive disorder (OCD), post-traumatic stress disorder (PTSD), and social anxiety disorder (SAD). Transient increases in hemodynamic activity have been reported during and after ketamine treatment, which may be desirable properties in some anesthesia settings, but are generally undesirable in psychiatric settings. While ketamine doses used in psychiatry are lower than those used in anesthesia, there are published instances of early termination of psychiatric ketamine infusions due to elevations in blood pressure and heart rate. No unifying study has been conducted to examine the impact of sub-anesthetic ketamine doses on hemodynamic parameters (systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR)) in psychiatric populations and to evaluate these changes across adult age groups. Here, data from 15 articles comprising a total N = 2252 ketamine or esketamine treatments in adult participants were used to conduct a meta-analysis of treatment-induced hemodynamic changes. Ketamine/esketamine produced modest but significant increases in the variables of interest with an average SBP increase of 12.61 mm Hg (95% CI 10.40 mm Hg to 14.82 mm Hg, z= 11.18, p< 0.0001), average DBP increase of 8.49 mm Hg (95% CI 6.89 mmHg to 10.09 mmHg, z= 10.41, p< 0.0001), and average heart rate increase of 4.09 beats per minute (95% CI 0.55 BPM to 7.63 BPM), z= 2.27, p= 0.0235). Stratified subgroup analysis indicated no significant differences between ketamine and esketamine effects on blood pressure. Further analysis indicated that there was no significant effect of age on ketamine-induced changes in SBP, DBP, and HR. Taken together these data show that sub-anesthetic ketamine and esketamine induce small but significant increases in hemodynamic parameters that are transient in nature in adult psychiatric populations. While these data are reassuring, it is important for each treatment case to fully explore potential cardiovascular risks prior to initiating treatment.